Bullying in Islamic Education Perspective of Alquran Hadith - Muhammad Habib Zainul Huda; Abdul Matin bin Salman (Institut Dirosat Islamiyah Al-Amien Prenduan, 2023)
The rise of bullying cases in the world of education encourages the author to analyze the case through the perspective of the Quran Hadith. The purpose of this study is none other than to find out how true bullying is according to the Quran Hadith and how the solution is. The author in this study uses Fazlur Rohman's Doable Movement Theory, the theory has two ways of working, namely First Movement (First Movement), and Seccond Movement (Second Movement), the theory is used to analyze how to solve contemporary era problems by looking at classical era problems. The results of this study include: 1) There are several types of bullying perspective of the Quran Hadith, including: making fun (suhriyah), denouncing (lams), calling bad (tanabuz), berating (shatam), slander (qodaf), persecute (dhorob), and kill (shafak). 2) The solution of the Quran Hadith in response to bullying in Islamic Education is to increase understanding of the Alquran and Hadith in the teaching-learning process, and also to emulate the attitude of the Prophet Muhammad Saw when faced with problems with others, which include his attitude, namely: advising, caring, musawah, forgiving, praying, not retaliating, silence, not grudges, aware of losses in the world and the hereafter. With this conclusion, this research is expected so that educators (Agents Of Change) always educate their students about how bad bullying is for themselves and for others. This education can be done through the approach of the Alquran and Hadith.